2010
DOI: 10.4061/2011/920958
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide and Related‐Sphingolipid Levels Are Not Altered in Disease‐Associated Brain Regions of APPSL and APPSL/PS1M146L Mouse Models of Alzheimer′s Disease: Relationship with the Lack of Neurodegeneration?

Abstract: There is evidence linking sphingolipid abnormalities, APP processing, and neuronal death in Alzheimer's disease (AD). We previously reported a strong elevation of ceramide levels in the brain of the APPSL/PS1Ki mouse model of AD, preceding the neuronal death. To extend these findings, we analyzed ceramide and related-sphingolipid contents in brain from two other mouse models (i.e., APPSL and APPSL/PS1M146L) in which the time-course of pathology is closer to that seen in most currently available models. Conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 66 publications
2
11
0
Order By: Relevance
“…These alterations were exacerbated in aged transgenic mice as compared with wild type controls, suggesting a correlation between aged cortical neuronal lipid raft detriment and AD phenotype. Alterations in the contents of long-chain ceramides and cholesterol have also been observed in another transgenic mouse model of AD (APP SL /PS1Ki), in correlation with similar results obtained in human AD cortex [80,81].…”
Section: Lipid Raft Stability and Progressive Neurodegenerationsupporting
confidence: 84%
“…These alterations were exacerbated in aged transgenic mice as compared with wild type controls, suggesting a correlation between aged cortical neuronal lipid raft detriment and AD phenotype. Alterations in the contents of long-chain ceramides and cholesterol have also been observed in another transgenic mouse model of AD (APP SL /PS1Ki), in correlation with similar results obtained in human AD cortex [80,81].…”
Section: Lipid Raft Stability and Progressive Neurodegenerationsupporting
confidence: 84%
“…Furthermore, an accumulating body of evidence consistently reported a global rise inCer levels in speci c brain regions of AD patients (13,71,72). In agreement with these observations, we found that 5xFAD transgenic mice at 6 months of age also showed an increase of Cer d18:1/16:0 in the cortex and ofseveral Cerspecies in the hippocampus (Cer d18:1/16:0, Cer d18:1/18:1, Cer d18:1/20:0 andCer d18:1/22:0).Previously, other studies showed increased brain Cer levels indifferenttransgenic AD models (APP, PS1, and PS1-APP mutated mice) (73).This suggests that there is a causal relationship between amyloid pathology and Cer imbalance.…”
Section: Discussionmentioning
confidence: 60%
“…The APPSL–PS1Ki mouse model is differentiated from other AD mouse models in its drastic neuronal loss, in part due to N-terminal truncated amyloid-β variants. Notably, in other mouse models, including APPSL, APPSL–PS1M146L and APPsw, in which there is not extensive early neuronal loss, ceramides were not found to be increased in the cortex or hippocampus [48,49]. Thus, similar to the discussion with tau above, amyloid-β-induced ceramide increases can lead to subsequent neurodegeneration.…”
Section: Cell and Animal Studies Suggest Sphingolipids Contribute To Almentioning
confidence: 60%